TB osteomyelitis - Keane, Joseph; Mc Laughlin, Anne (Oxford Univ Press, 2016)
Osteoarticular TB is very rare and as such, physicians are less experienced in diagnosing osteoarticular TB. This is compounded by the fact that the diagnosis of osteoarticular TB is difficult to achieve. Therefore, awareness and high index of suspicion of the disease is essential and referral to expertise should be made if diagnosis is indeterminate despite extensive investigations.
PUBLISHED
Keywords: Osteomyelitis; Tuberculosis